Reformation of Slums - MODUPE ODEMAKIN; ABIOLA AYOPO ABIODUN (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
The world keeps getting better in every aspect including housing and infrastructure and the growing technology keeps improving affordable housing, but the chances of completely eradicating slums will remain slim because there will always be people unable to afford better housing than slums have to offer. Aside from the fact that a slum is known as being the residential environment with the poorest living conditions, it is also known for various negative activities and a relatively high crime rate. The notion that an environment greatly influences an individual holds out the necessity to create better living conditions that will in time nurture and improve the individual. To this end, the reformation of slums should be a priority. In as much as these slums cannot be eradicated completely, physical upgrading of slums with improved street networks, better building materials, better air quality, easy access to basic municipal services, improves natural ventilation, natural lighting and better drainages will prove to make positive changes economically, socially and reduce crime rates in many cities. It will also improve the physical general wellbeing of communities. In conclusion, a community, no matter how small has the ability to influence the general well-being of an entire nation. Paying a little more attention to the physical reformation of slums will positively affect the world at large in the long run.